Law, Liberty, and the Pursuit of Terrorism. - Douglas, Roger (Ann Arbor : University of Michigan Press, 2014)
In democratic states, the courts can help safeguard civil liberties against excessive legislative and executive efforts to combat terrorism.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books